Becoming a Social Worker: Realising a Shared Approach to Professional Learning?. (9th February 2018) - McCulloch, Trish; Taylor, Susan
Abstract: Social work education has again been subject to scrutiny and review across the UK. Different countries have set about this task in different ways. In England, we can observe a top-down process driven by government; in Scotland, the approach has evolved more collaboratively. This paper discusses the recent Review of Social Work Education in Scotland within the broader pressures and opportunities of public service reform. At the heart of the review findings is a simple but timely conclusion: we need to realise a shared approach to professional learning, across the social work career path. This means moving beyond recent preoccupations with social work education, and polarising approaches to reform, towards a genuinely co-owned approach in which professional learning is a shared responsibility and a central feature of what it is to be a social work professional. In closing, the paper considers how we might realise a shared approach to professional learning in Scotland and beyond.